Meningkatkan Hasil Belajar Pola Bilangan Dengan Menggunakan Model Pembelajaran Numbered Heads Together - Irwan, Irwan; Zuhri, Zuhri; Perangin-Angin, Arsip (JURNAL PENA EDUKASI, 2021)
Abstract: This study discusses improving students' mathematics learning outcomes through the application of the NHT (Number Heads Together) type of cooperative learning model on the number pattern material in class VIII of SMP Negeri 3 Kutalimbaru. The problems in this study are that students have not been able to cooperate in learning mathematics, students feel bored and have difficulty when studying mathematics, and students' mathematics learning outcomes are not as expected (still low). This study took the research subjects of class VIII-1 semester I SMP Negeri 3 Kutalimbaru totaling 31 students. Based on the results of the study, it can be concluded that the application of the NHT type cooperative learning model can improve the learning outcomes of the number pattern material in class VIII students of SMP Negeri 3 Kutalimbaru. This is evidenced by an increase in the average score of students from cycle I to cycle II. From the average value of learning outcomes in the first cycle, which is 72.16, it increases in the second cycle to 80.52. Judging from the classical learning completeness also experienced an increase, in the first cycle of action the percentage of classical learning completeness was 61.29% increased in the second cycle to 90.22%. Keyword: Number Heads Together; number pattern  Abstrak: Penelitian ini membahas tentang meningkatkan hasil belajar matematika siswa melalui penerapan model pembelajaran kooperatif tipe NHT (Number Heads Together) pada materi pola bilangan di kelas VIII SMP Negeri 3 Kutalimbaru. Permasalah dalam penelitian ini yaitu siswa belum mampu untuk bekerjasama dalam pembelajaran matematika, siswa merasa bosan dan kesulitan ketika mempelajari matematika, dan hasil belajar matematika siswa tidak seperti yang diharapkan (masih rendah). Penelitian ini mengambil subjek penelitian siswa kelas VIII-1 semester I SMP Negeri 3 Kutalimbaru yang berjumlah 31 orang siswa. Berdasarkan hasil peneitian dapat disimpulkan bahwa penerapan model pembelajaran kooperatif tipe NHT dapat meningkatkan hasil belajar materi pola bilangan pada siswa kelas VIII SMP Negeri 3 Kutalimbaru. Hal tersebut dibuktikan dengan adanya peningkatan nilai rata-rata siswa dari siklus I ke siklus II. Dari nilai rata-rata hasil belajar pada siklus I yaitu sebesar 72,16 meningkat pada siklus II menjadi 80,52. Dilihat dari ketuntasan belajar klasikal juga mengalami peningkatan, pada tindakan siklus I yaitu persentase ketuntasan belajar klasikal sebesar 61,29% meningkat pada siklus II menjadi 90,22%. Kata kunci: Number Heads Together; pola bilangan